XRD and TG-FTIR study of the effect of mineral matrix on the pyrolysis and combustion of organic matter in shale char. (1st January 2015) - Fan, Chao; Yan, Junwei; Huang, Yiru; Han, Xiangxin; Jiang, Xiumin
Highlights: Minerals in shale char and its ashes are identified by XRD test. The pyrolysis and combustion processes can be divided into two stages. Confinement effect of mineral matrix slows the pyrolysis of organic matter. Minerals promote the oxidation of organic matter in two aspects. Oxidation of new organic sulfur compounds is hindered by minerals. Abstract: Shale char organic matter was obtained by demineralization of shale char through HCl and HF treatment. XRD technique was applied to determine the minerals in shale char and its ashes from different-temperature combustions. The effect of mineral matrix in shale char on the pyrolysis and combustion of organic matter was explored by the TG-FTIR test to shale char and its organic matter. Minerals in shale char ash changed both in amount and variety during combustion. Both the pyrolysis and combustion of shale char and its organic matter can be divided into two stages. Without confinement of mineral matrix after demineralization, the emission of gaseous products from the pyrolysis of shale char organic matter starts earlier than that of shale char pyrolysis. The effect of inorganic minerals on the oxidation of organic matter displays in two aspects. For one, the earth metal cations contained in inorganic minerals may promote the oxidation of organic matter. Secondly, the presence of inorganic matrix enhances the porosity of shale char. New organic sulfur formed during oil shale retorting is confined by inorganic matrix during combustion. After demineralization, this new organic sulfur can decompose and be released intensively at low temperature.